2016
DOI: 10.1177/0021909616649211
|View full text |Cite
|
Sign up to set email alerts
|

Urban Transition in West Bengal, India

Abstract: Contemporary urbanization in India is in transition and this, along with the continuation of a ‘top heavy’ urban structure and gradual deindustrialization, is characterized by faster growth of informal employment, a declining trend of urban-ward migration of males, the slow down in the growth of cities and towns and the emergence of new urban centres. Given this immediate backdrop, this paper examines the contemporary processes and emerging forms of urban transition in West Bengal, with its longstanding histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…The urbanization pattern in this region is similar to McGhee's Desakota model (type 3). The region experienced high population growth, decline in the proportion of population engaged in agricultural activities, concurrent growth of small to medium-sized industries, and slower overall economic growth (Guin, 2017;Mondal, Das, & Dolui, 2015;Mukherjee, 2011;Sud, 2014). Unlike the Delhi and Mumbai urban agglomerations, the growth of Kolkata UA does not share the same degree of influence of colonial legacy (Guin, 2017).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The urbanization pattern in this region is similar to McGhee's Desakota model (type 3). The region experienced high population growth, decline in the proportion of population engaged in agricultural activities, concurrent growth of small to medium-sized industries, and slower overall economic growth (Guin, 2017;Mondal, Das, & Dolui, 2015;Mukherjee, 2011;Sud, 2014). Unlike the Delhi and Mumbai urban agglomerations, the growth of Kolkata UA does not share the same degree of influence of colonial legacy (Guin, 2017).…”
Section: Study Areamentioning
confidence: 99%
“…The region experienced high population growth, decline in the proportion of population engaged in agricultural activities, concurrent growth of small to medium-sized industries, and slower overall economic growth (Guin, 2017;Mondal, Das, & Dolui, 2015;Mukherjee, 2011;Sud, 2014). Unlike the Delhi and Mumbai urban agglomerations, the growth of Kolkata UA does not share the same degree of influence of colonial legacy (Guin, 2017). However, more than 300 years of urbanization, projected high economic growth (Brar et al, 2014), and the potential threat of sea-level rise (Satterthwaite, 2007) provide an opportunity to explore the local and regional drivers of urbanization and the future patterns of urban growth.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…They are forced to quit farming, and pushed to take on alternative livelihoods in the rural nonfarm economy (also see Khasnabis, 2008). However, as Guin (2016) argues, many of these small urban spaces have a weak economic base and generally lack industrial sectors of any significance, making it difficult for former agrarian laborers to find suitable alternative employment.…”
Section: Introductionmentioning
confidence: 99%
“…Keeping in view this unfavourable condition for rural transformation, Kundu (2011), soon after the publication of the urban data of census 2011, argued that this unprecedented increase of CTs was attributed to artificial inflation by the census authority (i.e., 'census activism'). However, subsequent studies (Guin 2017;Guin andDas 2015a, 2015b;Mitra and Kumar 2015;Pradhan 2013) have found no reason to rely on the thesis of 'census activism' as a majority of the new CTs had met the census-laid criteria right back in 2001. In this backdrop, the present study, on the basis of a case study of a new CT, tries to throw some light on the processes of transformation of the villages which have got the status of CTs in the current census.…”
Section: Introductionmentioning
confidence: 99%